THE MODIFIED MULTIFACTORIAL INTERVENTION PROGRAM FOR COMMUNITY-DWELLING OLDER ADULTS WITH KNEE OSTEOARTHRITIS: A COMPARATIVE STUDY BETWEEN PERSONS WITH MILD AND MODERATE SYMPTOMS - Kankayant, Chatsuda; Aree-Ue, Suparb; Youngcharoen, Phichpraorn; Kawinwonggowit, Viroj (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This quasi-experimental research aimed to investigate the effect of an application of the Modified Multifactorial Intervention Program (mMUFIP) on knowledge about knee osteoarthritis (OA), knee OA illness representation, psychological well-being, and health outcomes (knee pain and knee range of motion) of community-dwelling older adults with knee OA. The samples consisted of 50 participants, evenly divided into two experimental groups: Group 1 and Group 2, which were people with mild and moderate symptoms, respectively. Both groups received the mMUFIP program consisting of health education about knee OA, weight reduction/control, quadriceps exercise, and home visits. The participants had been monitored for eight weeks after they enrolled in the intervention program. Data were collected using self-reporting questionnaires and health assessments and analyzed using descriptive statistics, Chi-square, and MANCOVA repeated measures. The results revealed that participants in both groups had a better mean score of knowledge about knee OA, illness representation of knee OA, and health outcomes (knee pain and knee range of motion) at the eighth week than the baseline with a significant difference (p < .05). Comparing the two groups, it was found that the mean scores of knowledge about knee OA, illness representation of knee OA, and health outcomes (knee pain and knee range of motion) were not significantly different. It is suggested that the mMUFIP can be used for older adults with knee osteoarthritis who have mild and moderate symptoms to promote better health outcomes.